Effect of NPK Dose (16:16:16) on Growth and Yield of Cayenne Chili (Capsicum frutescens L.) in Tasikmalaya - Adinda Putri Amanda; Muhammad Agus Mulyana; Aulia Wahyuningtyas (Jurnal Biologi Tropis, 2023)
Cayenne pepper (Capsicum annum L.) is one type of chili that has high demand in Tasikmalaya. To fulfill the consumption, cayenne pepper production is needed to be added. This study helps to determine the best dose of NPK fertilizer that can support the growth yield of cayenne pepper, especially in Tasikmalaya. The research was conducted in experimental field of Agriculture Faculty Universitas Perjuangan Tasikmalaya from November 2022 until February 2023. Experimental design used a randomized block degisn of single factor with six treatments and three replications. The treatments consist of no NPK fertilizer, ( ¼ , ½ , ¾ , 1 and 1 ¼ ) doses of NPK fertilizer.  The results showed that NPK fertilizer had an affect on plant hight with 15.6 cm (3 WAP), 20.4 cm (4 WAP), 24,5 (5 WAP), 27,5 (6 WAP) and 29.5 cm (7 WAP).  The highest cumulative yield of cayenne pepper from  1st until 3th harvests with fruit weight plant-1 was the 1 dose NPK treatment of 358,08 g plant-1.